2x-9=-9

Simple and best practice solution for 2x-9=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-9=-9 equation:


Simplifying
2x + -9 = -9

Reorder the terms:
-9 + 2x = -9

Add '9' to each side of the equation.
-9 + 9 + 2x = -9 + 9

Combine like terms: -9 + 9 = 0
0 + 2x = -9 + 9
2x = -9 + 9

Combine like terms: -9 + 9 = 0
2x = 0

Solving
2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| x^42=13 | | -2(3b+3)+(7b-8)=0 | | -5k^2+11k+52=4k | | 6=-6y+3(y+8) | | x-3=10x+30 | | 12x+16=12x-84 | | -7(-15)= | | -12x^2+x=3-4x^2+9x | | (3,-10)= | | 6x-3(x-1)=2x | | -10+4x=-10 | | 2x*3x=2 | | 9+x=5 | | 4(4-n)=6n-4 | | -6=x+3 | | Y-8=-16 | | 2.7q-2.6-1.8q=0.1q-4.3 | | 3r-8=32 | | 2m^2-9m-18=0 | | x^2+5x+5x+18=9 | | H=2r-16 | | 10+x=4 | | 3d+9=6d-12 | | 12+2c+9c-6-11c= | | 12y+3=7 | | b^2-8b-58=0 | | -4n+3-7n= | | 15y-6=11 | | 8-5+j=67 | | 9y=3y | | 25w^2-x^2=0 | | -12+8m-6+1=1+5m+6m |

Equations solver categories